Bio-based nanomaterials and their biomedical applications: a short review - Sezalia, Nur Atirah Afifah; Ong, Hui Lin; Villagracia, Al Rey; Hoang, Tuan-Dung (Vietnam Journal of Science and Technology, 2024)
Recent advancements in biomedical technologies have led to the exploration of bio-based nanomaterials, which offer exceptional properties such as high surface area, biocompatibility, and environmental friendliness. Additionally, the bio-based nanomaterials are widely available and provide a sustainable architecture for various applications. This review highlights three distinct nanomaterials synthesized from and/or with bio-sources: nanocellulose, silver nanoparticles, and carbon dots/carbon quantum dots, representing natural polymers, metallic nanoparticles, and organic nanoparticles, respectively. This review discusses their synthesis methods and their potential applications in tissue engineering, wound healing, and biosensing. The review also includes an outlook on the utilization and challenges of these nanomaterials in biomedical applications.